Efektivitas Pemberian Suplemen Zat Besi Terhadap Kadar Hemoglobin Ibu Hamil: Literatur Review - Tifani Hadi Tri Wahyuni (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Anemia in pregnant women remains a global public health problem, particularly in developing countries. Iron supplementation is the main intervention recommended for the prevention and management of anemia during pregnancy. This literature review aims to analyze the effectiveness of iron supplementation in preventing anemia among pregnant women using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Article searches were conducted through scientific databases and the attached journals, with a publication range from 2019 to 2024. The selection process resulted in 10 articles that met the inclusion criteria. Narrative synthesis showed that iron supplementation, whether administered alone or combined with vitamin C or other supportive nutritional interventions, was effective in increasing hemoglobin levels in pregnant women. Adherence to supplementation and nutritional education support were significant factors influencing the success of the intervention.